THE IMPLEMENTATION OF DEEP APPROACH IN TEACHING ANALYTICAL EXPOSITION WRITING TO ELEVENTH GRADERS AT SMAN 1 BOJONEGORO (RETAIN, 2017)
THE IMPLEMENTATION OF DEEP APPROACH IN TEACHING ANALYTICAL EXPOSITION WRITING TO ELEVENTH GRADERS AT SMAN 1 BOJONEGORO Hanis Septin Ilhamy English Department, Languages and Arts Faculty, The State University of Surabaya Email:hanisilhamy@mhs.unesa.ac.id Fauris Zuhri S.Pd., M.Hum. English Department, Languages and Arts Faculty, The State University of Surabaya Email: fauriszuhri@unesa.ac.id Abstract The goal of this research is to describe the use of deep approach as a writing strategy to the students in senior high school with the special attention to the teaching of Analytical Exposition writing. The students’ feeling toward the use of deep approach as their writing strategy to write Analytical Exposition text is also observed. The research design in this research was descriptive qualitative, that is used to answer question related to the use of deep approach as strategy to teach analytical exposition writing at eleventh graders in SMAN 1 Bojonegoro and the students’ feeling toward the use of deep approach itself. The research instruments used in this research were fieldnotes, observation checklist, and questionnaire. Relating to the result and discussion, the use of deep approach as strategy to teach analytical exposition writing at eleventh graders in SMAN 1 Bojonegoro can be applied using three steps, which are opening, main activity, and closing. The broad idea and detailed information can be successfully discovered by following the steps in deep approach. The students also give positive response toward the use of deep approach as strategy to teach analytical exposition writing. Keywords: Writing, Analytical Exposition text,Deep Approach Abstrak Tujuan dari penelitian ini adalah untuk menjelaskan penggunaan “Deep Approach” dengan kajian khusus penggunaan pendekatan untuk teks Analytical Exposition sekolah menengah atas serta respon siswa terhadap penggunaan pendekatan tersebut. Kualitatif analisis di gunakan untuk menganalisis penggunaan pendekatan mendalam serta respon siswa terhadap penggunaan pendekatan tersebut. Fieldnotes, observation checklist, dan kuisioner di gunakan sebagai instrumen penelitian. Hasil yang diperoleh menunjukkan bahwa “Deep Approach” dapat di terapkan melalui tiga langkah yaitu pengumpulan ide, perefleksian ide dengan dunia nyata, dan penyusunan karangan. Siswa memberi respon positif melalui siakp antusias dalam kegiatan belajar mengajar dan hasil maksimal yang di peroleh dalam pengajaran menggunakan “Deep Approach”. Kata Kunci : Deep approach, Teks analytical exposition